Stimulating Managerial Capital in Emerging Markets : The Impact of Business and Financial Literacy for Young Entrepreneurs - Bruhn, Miriam; Zia, Bilal (2012)
Identifying the determinants of entrepreneurship is an important research and policy goal, especially in emerging market economies where lack of capital and supporting infrastructure often imposes stringent constraints on business growth. This paper studies the impact of a comprehensive business and financial literacy program on firm outcomes of young entrepreneurs in an emerging post-conflict economy, Bosnia and Herzegovina. The authors conduct a randomized control trial and find that while the training program did not influence business survival, it significantly improved business practices, investments, and loan terms for surviving businesses. Entrepreneurs with higher ex-ante financial literacy further exhibited some improvements in business performance and sales.